2018
DOI: 10.1002/ceas.12098
|View full text |Cite
|
Sign up to set email alerts
|

Interview Experiences and Diversity Concerns of Counselor Education Faculty From Underrepresented Groups

Abstract: The authors used transcendental phenomenology to explore the campus interview experiences and diversity concerns of counselor education faculty from underrepresented populations. Six themes were identified: issues of integrity, disappointment in the counseling profession, importance of authenticity, intersectionality of major identity markers, competence, and supportive experiences. Findings suggest that culturally competent search committees should be aware of biases and policies promoting institutional and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Examples of qualitative studies may include phenomenological investigations into the experiences of faculty of color in planning and carrying out study-abroad programs, consensual qualitative research studies identifying best practices for RCT study abroad, study-abroad programs, although resources such as the FEA standards and empirical work by Ng et al (2012) provide a foundation for counselor educators to develop competencies specific to counseling studyabroad programs. As part of their normal duties, faculty already manage research, teaching, and service responsibilities, which can sometimes be overwhelming (Cartwright et al, 2018;Wester, 2019). Thus, embarking on a study-abroad program, especially if it is as time-consuming and emotionally demanding as the one described in this article, may seem risky, and the benefits to faculty may not readily be seen.…”
Section: Recommendations For Future Research and Program Planningmentioning
confidence: 98%
See 2 more Smart Citations
“…Examples of qualitative studies may include phenomenological investigations into the experiences of faculty of color in planning and carrying out study-abroad programs, consensual qualitative research studies identifying best practices for RCT study abroad, study-abroad programs, although resources such as the FEA standards and empirical work by Ng et al (2012) provide a foundation for counselor educators to develop competencies specific to counseling studyabroad programs. As part of their normal duties, faculty already manage research, teaching, and service responsibilities, which can sometimes be overwhelming (Cartwright et al, 2018;Wester, 2019). Thus, embarking on a study-abroad program, especially if it is as time-consuming and emotionally demanding as the one described in this article, may seem risky, and the benefits to faculty may not readily be seen.…”
Section: Recommendations For Future Research and Program Planningmentioning
confidence: 98%
“…Cartwright, Avent-Harris, Munsey, and Lloyd-Hazlett (2018) found that counselor education faculty from underrepresented groups face unique challenges in their respective programs at universities across the United States. Specifically, faculty of color report the need for supportive, authentic relationships with colleagues and students to enhance and sustain their professional endeavors (Cartwright et al, 2018). From an RCT perspective, authenticity is necessary for genuine engagement (Jordan, 2018).…”
Section: Case Illustrationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors explored diversity and inclusion and its impact on curriculum, arguing that cultural immersion experiences (Shannonhouse, Myers, & Barrio Minton, 2018), military culture (Carter & Watson, 2018), spiritually transformative experiences (Blalock & Holden, 2018), and sexual identity development (McDonald, Kelly, & Dotson‐Blake, 2018) should be included in the curriculum. Additionally, some authors offered suggestions for interventions to be used in the classroom, including growth groups (Zhu, 2018), creative interventions to increase empathy (Bell, 2018), video grand rounds (Crowe, Dotson‐Blake, Vazquez, & Malone, 2018), community service learning projects (Lloyd‐Hazlett, 2018), and self‐compassion as self‐care (Nelson, Hall, Anderson, Birtles, & Hemming, 2018). Rapp, Moody, and Stewart (2018) presented recommendations for attending to gatekeeping in doctoral curricula.…”
Section: Teaching and Trainingmentioning
confidence: 99%
“…Diversity and inclusion research about counselor educators included quantitative investigation of mothers’ occupational satisfaction (Neale‐McFall, Eckart, Hermann, Haskins, & Ziomek‐Daigle, 2018). Qualitative inquiries included experiences of “minoritized” (Pérez & Carney, 2018, p. 162) faculty members with institutional oppression and campus interviews (Cartwright, Avent‐Harris, Munsey, & Lloyd‐Hazlett, 2018), as well as analyses of African American male counselors’ social justice efforts (Dollarhide et al, 2018) and actions of LGBTQ+ competent faculty members (Gess & Doughty Horn, 2018).…”
Section: Understanding Stakeholdersmentioning
confidence: 99%